Disability-adjusted life years due to chronic and hidden hunger under food system evolution with climate change and adaptation to 2050 - Sulser, Timothy B.; Beach, Robert H.; Wiebe, Keith D.; Dunston, Shahnila; Fukagawa, Naomi K. (Oxford University Press, 2021)
Background: Climate change presents an increasing challenge for food-nutrition security. Nutrition metrics calculated from quantitative food system projections can help focus actions. Objectives: To estimate future chronic and hidden hunger disability-adjusted life years (DALYs)-due to protein-energy undernutrition and micronutrient deficiencies, respectively-using food systems projections to evaluate the potential impact of climate change and agricultural sector investment for adaptation. Methods: We use a novel combination of a chronic and hidden hunger DALY estimation procedure and food system projections from quantitative foresight modeling to assess DALYs under alternative agricultural sector scenarios to midcentury. Results: Total chronic and hidden hunger DALYs are projected to increase globally out to 2050-by over 30 million compared with 2010-even without climate change. Climate change increases total DALY change between 2010 and 2050 by nearly 10% compared with no climate change. Agricultural sector investments show promise for offsetting these impacts. With investments, DALY incidence due to chronic and hidden hunger is projected to decrease globally in 2050 by 0.24 and 0.56 per 1000 capita, respectively. Total global DALYs will still rise because projected population growth will outpace the rate reduction, especially in Africa south of the Sahara. However, projections also show important regional reductions in total DALYs due to chronic (13.9 million in South Asia, 4.3 million in East Asia and the Pacific) and hidden hunger (7.5 million in East Asia and the Pacific) with investments. Conclusions: Food system projections to 2050 show a decreasing DALY incidence from both chronic and hidden hunger. Population growth is projected to outpace these improvements and lead to increasing total chronic and hidden hunger DALYs globally, concentrated in Africa south of the Sahara. Climate change increases per-capita chronic and hidden hunger DALY incidence compared with no climate change. Agricultural sector investments show the potential to offset the climate impact on DALYs.